Ceramic Robocasting: Recent Achievements, Potential, and Future Developments. Issue 47 (10th October 2018) - Peng, Erwin; Zhang, Danwei; Ding, Jun
Abstract: Additive manufacturing (AM) of ceramic materials has attracted tremendous attention in recent years, due to its potential to fabricate suitable advanced ceramic structures for various engineering applications. Robocasting, a subset of ceramic AM, is an ideal technique for constructing fine and dense ceramic structures with geometrically complex morphology. With the freedom and convenience to deposit various materials within any 3D spatial position, ceramic robocasting opens up unlimited opportunities, which are otherwise hardly attainable from other AM techniques. Here, a summary of the recent progress on the fabrication of single and multi‐ceramic structures by robocasting is provided, as well as the prospects of achieving shapeable ceramic structures. The current challenges in ceramic robocasting and an outlook on its development, especially toward the fabrication of self‐shaping ceramic structures, are also discussed. Abstract : Ceramic robocasting is widely employed to fabricate various advanced ceramic materials due to its versatility. Recent ceramic robocasting development is discussed, including the current trends and strategies toward the fabrication of shapeable and geometrically complex ceramic structures. The current challenges and outlook on ceramic robocasting, especially toward the additive manufacturing of self‐shaping ceramic structure, are highlighted.